Pengembangan Bahan Ajar Sistem PeredaranDarah Manusia Berbasis Flipbook untuk Meningkatkan Kesadaran Metakognitif Siswa SMA Negeri 3 Makassar - Bahri HS, Syamsul; Adnan, Adnan; Idris, Irma Suryani (Biology Teaching and Learning, 2019)
Abstract.The research model used is Research and Development (R & D) which aims to produce flipbook-based electronic teaching materials that are integrated with valid curriculum and content standards. The subjects of this study were 2 persons biology teacher, and thirty-one students in class XI SMA 3 Makassar. This research was carried out by using the modification of the ADDIE development model which consisted of the stages of Analyze, Design, Dvevelopment, Implementation, and Evaluation. The data collected is data on the results of the flipbook-based electronic teaching material validation obtained from media and material expert validation questionnaires, the practicality obtained from the questionnaire tested through students and teachers, and the results of effectiveness obtained from the metacognitive awareness questionnaire and test results filled by students of class XI MIA 1 SMA Negeri 3 Makassar. Data obtained from the results of the study were analyzed using descriptive statistical analysis. Flipbook-based electronic teaching materials. developed has several components such as learning material, animation and learning videos, pictures, practice questions, and evaluation questions. The results of the study show that the average value of the total validity of flipbook-based electronic teaching materials as a whole is in the very valid category (4.59). The overall student response is in a very practical category (4.14). Teacher response is in a very practical category (4.28). The overall metacognition awareness of students is in the good category (3.97). Based on the results of this study, it can be concluded that the flipbook-based electronic teaching material for class XI high school studied has a high level of validity.Keywords:learning materials, e-books, metacognitive, development.